2016
DOI: 10.1182/blood-2015-10-678706
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Rho-associated kinase 2 inhibition suppresses murine and human chronic GVHD through a Stat3-dependent mechanism

Abstract: • The ROCK2 inhibitor, KD025, decreases chronic GVHD pathology in multiple murine models.• KD025 inhibits STAT3 phosphorylation to decrease RORgt and Bcl6 expression in both murine and human cells.Chronic graft-versus-host disease (cGVHD) remains a major complication following allogeneic bone marrow transplantation (BMT). The discovery of novel therapeutics is dependent on assessment in preclinical murine models of cGVHD. Rho-associated kinase 2 (ROCK2) recently was shown to be implicated in regulation of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
165
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 153 publications
(173 citation statements)
references
References 42 publications
4
165
0
4
Order By: Relevance
“…In agreement with previous findings in animal models and Th17-skewing in vitro culture of human T cells (15)(16)(17), this study further confirmed the potential of selective ROCK2 inhibition to downregulate autoimmune-driven pathology via shifting the balance between proinflammatory and anti-inflammatory immune cell responses. Although the clinical improvement achieved in the same time span by treatment with KD025 was not as robust as the response seen with other oral treatments, such as methotrexate, JAK inhibitors, and apremilast, or newer biologics neutralizing cytokines in the Th17 pathway, future randomized trials of KD025 carried out for a longer time period (to account for a different molecular mechanism of action) in a larger population of psoriatic patients are required to further validate the therapeutic potential and risk-benefit profile of targeted ROCK2 inhibition in psoriasis.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…In agreement with previous findings in animal models and Th17-skewing in vitro culture of human T cells (15)(16)(17), this study further confirmed the potential of selective ROCK2 inhibition to downregulate autoimmune-driven pathology via shifting the balance between proinflammatory and anti-inflammatory immune cell responses. Although the clinical improvement achieved in the same time span by treatment with KD025 was not as robust as the response seen with other oral treatments, such as methotrexate, JAK inhibitors, and apremilast, or newer biologics neutralizing cytokines in the Th17 pathway, future randomized trials of KD025 carried out for a longer time period (to account for a different molecular mechanism of action) in a larger population of psoriatic patients are required to further validate the therapeutic potential and risk-benefit profile of targeted ROCK2 inhibition in psoriasis.…”
Section: Resultssupporting
confidence: 79%
“…ROCK2 is induced during Th17-skewing conditions and regulates IL-17 secretion via a STAT3/IRF4/RORgtdependent mechanism in mice and humans (13,(15)(16)(17). Histological assessment revealed that baseline pSTAT3, IRF4, RORgt, and ROCK2 staining were greater, whereas ROCK1 expression was diminished in lesional skin in comparison with nonlesional skin (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have demonstrated a role for Th17 cells in murine models with features of autoimmunity (26), scleroderma (28), and multiorgan system disease with bronchiolitis obliterans (BO) in a CSF-1/CSF-1R-(29) and STAT3-dependent manner (30,31). In humans, there is a paucity of data.…”
Section: Introductionmentioning
confidence: 99%